Visions of charity : volunteer workers and moral community - Allahyari, Rebecca Anne, 1963- (University of California Press, 2000)
In the US, public talk about charity is highly moralistic, even in an era of welfare reform. This study looks at the front lines of volunteer involvement with the poor and homeless at two specific charities to assess what volunteer work means for those who do it.